2015 IEEE International Conference on Communications (ICC) 2015
DOI: 10.1109/icc.2015.7248526
|View full text |Cite
|
Sign up to set email alerts
|

Spatial separation of closely-spaced users in measured massive multi-user MIMO channels

Abstract: Abstract-Fully-synchronous measurements of a massive multi-user multiple-input multiple-output (MU-MIMO) radio propagation channel are presented. We evaluate the ability of a massive MIMO system to spatially separate users located close to each other in line-of-sight (LOS) propagation conditions. The system consists of a base-station (BS) antenna array equipped with 64 dual-polarized antenna elements (128 ports) arranged in a cylindrical configuration, and eight single-antenna users. The users are confined to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 18 publications
0
41
0
Order By: Relevance
“…For fixed N , we say that A outperforms B ifc A (ρ, N ) >c B (ρ, N ), where A and B may be applied to different scenarios. With one exception 6 , the relative sum-ratesc A (ρ, N ) increase with increasing values of N . At N = 128, D-SUB and H-SUB achieve the sum-capacity of the channel, and D-GOB and H-GOB achieve the sum-rate of ZF with perfect CSI.…”
Section: A Relative Sum-rate As a Function Of Nmentioning
confidence: 93%
See 2 more Smart Citations
“…For fixed N , we say that A outperforms B ifc A (ρ, N ) >c B (ρ, N ), where A and B may be applied to different scenarios. With one exception 6 , the relative sum-ratesc A (ρ, N ) increase with increasing values of N . At N = 128, D-SUB and H-SUB achieve the sum-capacity of the channel, and D-GOB and H-GOB achieve the sum-rate of ZF with perfect CSI.…”
Section: A Relative Sum-rate As a Function Of Nmentioning
confidence: 93%
“…The horizontal gap between the curves of D-GOB and H-GOB in Fig. 3, and between those of D-SUB and H-SUB, represents the penalty due to the frequency selectivity of the channel, in 6 In scenario 3, the relative sum-rate of H-GOB decreases slightly when N goes from 1 to 2. This can happen because ZF is used based on partial CSI.…”
Section: A Relative Sum-rate As a Function Of Nmentioning
confidence: 99%
See 1 more Smart Citation
“…The UCA is another popular antenna structure in massive MIMO systems. For multipolarized UCA massive MIMO systems, all the antennas are uniformly spaced on a circular edge as shown in Figure . In our proposed multipolarized UCA massive MIMO systems scheme, if antenna A m is vertically polarized antenna, antenna A m + 1 will be horizontally polarized antenna and vice versa.…”
Section: ‐D Channel Modeling Of Multipolarized Uca Massive Mimo Systemsmentioning
confidence: 99%
“…The results showed that most of the theoretical benefits of massive MIMO can be observed over the measured channels. The system performances of massive MIMO based on outdoor channel measurement campaigns were evaluated in Gao et al (2012;, Payami and Tufvesson (2012), and Flordelis et al (2015). The investigated frequency is 2.6 GHz and the bandwidth is 50 MHz.…”
Section: Introductionmentioning
confidence: 99%